Animal welfare: From concepts to reality - Volpato, Gilson Luiz [UNESP]; Giaquinto, Percília Cardoso [UNESP]; de Castilho, Marisa Fernandes; Barreto, Rodrigo Egydio [UNESP]; de Freitas, Eliane Gonçalves [UNESP] (Oecologia Australis, 2009)
In this review, we provide a brief retrospective history of the science of animal welfare and recognize the sentience of non-human animals; however, we emphasize that crucial problems remain regarding how to define and measure animal welfare. In general, the use of physiological measures to assess welfare is discouraged. Furthermore, there is a theoretical background for measures of stress, but not for welfare states because life may not be at risk. Instead, a preference or choice-based approach, which is based on the animal decision, is recommended. To this end, welfare is discussed and then contrasted with disease, health, stress and distress. In addition, the importance of prospective capacities for the welfare of human and non-human animals is discussed.
Bem-estar animal: Dos conceitos à realidade
Keywords: Choice; Disease; Distress; Health; Preference; Stress; Welfare; Well-being